Changes of Milk Production and Reproductive Performance of Dairy Buffaloes in Nepal During Recent 15 Years - Hayashi, Y.; Shah, M. K.; Kumagai, H. (Journal of Buffalo Science, 2014)
Consumption of buffalo milk has been increasing in Nepal. Thus, further development of dairy buffalo is required for efficient production. However, the changes of milk production and reproductive performance of buffaloes in the country remain obscure. Hence, the study is conducted for identifying the dairy production and reproduction of buffaloes raised in Nepal during 15 years. The records of daily milk yield (MY) from July 1997 to July 2012 were collected at Livestock Development Farm, Nepal. Lactation MY, 305 days MY, lactation length, MY per day of lactation, peak MY, days to attain peak MY, calving interval and dry period were calculated. The results were summarized every 5 years (Period 1: July 1997 – July 2002, Period 2: July 2002 – July 2007, Period 3: July 2007 – July 2012). The lactation MY, 305 days MY, daily MY per lactation and peak MY were lower in Period 1 than in Period 2 and 3. On the other hand, the days to attain peak MY was longer in Period 1 than in the other periods. However, the lactation length had no significant difference among the periods. The milk production was assumed to improve from Period 1 to Period 2 and 3. The calving interval was longer in Period 3 than in Period 2. The dry period was longest in Period 3. The efficiency of buffalo reproduction during the recent 5 years assumed to be declined. The deterioration of reproduction possibly has been caused by changes in nutritional and environmental conditions during the surveyed period.